Preliminary observations on the Levantine Aurignacian sequence of Manot Cave: Cultural affiliations and regional perspectives. Issue 160 (November 2021) - Marder, Ofer; Shemer, Maayan; Abulafia, Talia; Bar-Yosef Mayer, Daniella; Berna, Francesco; Caux, Solene; Edeltin, Lotan; Goder-Goldberger, Mae; Hershkovitz, Israel; Lavi, Ron; Shavit, Roi; Tejero, Jose-Miguel; et al.
Abstract: A well-preserved sequence of Early Upper Paleolithic (EUP) occupations has been revealed in the past decade in Manot Cave, the studies of which shed light on the cultural dynamics and subsistence patterns and paleoenvironment. Most intriguing is the series of overlying Levantine Aurignacian occupation layers, exposed near the entrance to the cave. Area E is considered the inner part of the main activity area in Manot Cave. Remains of intact combustion features, as well as numerous flint artifacts and faunal remains, were found, indicating a high level of preservation. Within a 2.5 m sequence, nine distinct occupation layers were defined. The presence of characteristic flint and osseous industries alongside a rich mollusk assemblage led to the initial association of the sequence as a whole to the Levantine Aurignacian. However, as research advanced and variability in the material culture became apparent, it became clear that a division of the sequence into two phases, early and late, is required. A preliminary study of the assemblage variability implies distinct changes in human behavior between the two phases. Most prominently, these are indicated by a change in bladelet production method and morphology alongside an increase in the significance of the bladelet component within the flint assemblage, the disappearance of composite osseous industries, and a steep decrease in mollusk shell representation in the late occupation phase. Radiocarbon dating indicates a short time span between the two phases. The earlier phase defined as, Levantine Aurignacian, was ascribed an age range of 38–34 ka cal BP with a more constrained age range of 37–35 ka cal BP suggested based on Bayesian models. In the late phase, which is temporarily referred to as "post-Levantine Aurignacian, " an age range of 36–33 ka cal BP is suggested.